Lipschitzian invariant tori of indefinite monotone system - Lagoda, V. A.; Parasyuk, I. O.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider a nonlinear system in the direct product of a torus and a Euclidean space. For this system, under the conditions of indefinite coercivity and indefinite monotonicity, we establish the existence of a Lipschitzian invariant section.